Targeting β‐catenin in hepatocellular cancers induced by coexpression of mutant β‐catenin and K‐Ras in mice. Issue 5 (6th February 2017) - Tao, Junyan; Zhang, Rong; Singh, Sucha; Poddar, Minakshi; Xu, Emily; Oertel, Michael; Chen, Xin; Ganesh, Shanthi; Abrams, Marc; Monga, Satdarshan P.
Abstract : Recently, we have shown that coexpression of hMet and mutant‐β‐catenin using sleeping beauty transposon/transposase leads to hepatocellular carcinoma (HCC) in mice that corresponds to around 10% of human HCC. In the current study, we investigate whether Ras activation, which can occur downstream of Met signaling, is sufficient to cause HCC in association with mutant‐β‐catenin. We also tested therapeutic efficacy of targeting β‐catenin in an HCC model. We show that mutant‐K‐Ras (G12D), which leads to Ras activation, cooperates with β‐catenin mutants (S33Y, S45Y) to yield HCC in mice. Affymetrix microarray showed > 90% similarity in gene expression in mutant‐K‐Ras‐β‐catenin and Met‐β‐catenin HCC. K‐Ras‐β‐catenin tumors showed up‐regulation of β‐catenin targets like glutamine synthetase (GS), leukocyte cell‐derived chemotaxin 2, Regucalcin, and Cyclin‐D1 and of K‐Ras effectors, including phosphorylated extracellular signal‐regulated kinase, phosphorylated protein kinase B, phosphorylated mammalian target of rapamycin, phosphorylated eukaryotic translation initiation factor 4E, phosphorylated 4E‐binding protein 1, and p‐S6 ribosomal protein. Inclusion of dominant‐negative transcription factor 4 at the time of K‐Ras‐β‐catenin injection prevented HCC and downstream β‐catenin and Ras signaling. To address whether targeting β‐catenin has any benefit postestablishment of HCC, we administered K‐Ras‐β‐catenin mice with EnCore lipid nanoparticles (LNP) loaded with a Dicer substrate small interfering RNA targeting catenin beta 1 (CTNNB1; CTNNB1‐LNP), scrambled sequence (Scr‐LNP), or phosphate‐buffered saline for multiple cycles. A significant decrease in tumor burden was evident in the CTNNB1‐LNP group versus all controls, which was associated with dramatic decreases in β‐catenin targets and some K‐Ras effectors, leading to reduced tumor cell proliferation and viability. Intriguingly, in relatively few mice, non‐GS‐positive tumors, which were evident as a small subset of overall tumor burden, were not affected by β‐catenin suppression. Conclusion : Ras activation downstream of c‐Met is sufficient to induce clinically relevant HCC in cooperation with mutant β‐catenin. β‐catenin suppression by a clinically relevant modality is effective in treatment of β‐catenin‐positive, GS‐positive HCCs. (Hepatology 2017;65:1581‐1599)